Plano de negócios Mega Academia - (:unkn) unknown (Brasil, 2023)
The idea for the business arose from the need seen in Laranjal do Jari, to open a gym that was concerned with meeting the needs of the client, thus focusing on health and well-being, physical performance and quality of life. Bearing these indicators in mind, the Mega Academia will have a place with equipment and machines for bodybuilding exercises, in addition to a place for zumba classes. The gym will be open from 6:00 am to 10:00 pm, which will result in 16 hours of operation, from Monday to Saturday. With this, the company will work with the monthly fee model that will correspond to the right to go to the gym one hour a day. In order to meet the needs of the company's target audience, Mega Academia will have a team of qualified professionals dedicated to monitoring the evolution process of each student according to their specificities. A survey was carried out of all the financial investments necessary for the implementation and execution of the business, namely: initial investment of R$ 957.434.04 (Nine hundred and fifty-seven thousand, four hundred and thirty-four and four cents); internal rate of return of: 25.70% (twenty-five point seventy percent) and also a payback period of 3 (three) years and 4 (four) months.
Keywords: Plano de negócio; Business plan; Mega academia; Mega academia; Qualidade de vida; Quality of life; CNPQ::CIENCIAS SOCIAIS APLICADAS